2006
DOI: 10.2987/8756-971x(2006)22[213:tafopn]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Anopheline Fauna of Papua New Guinea

Abstract: Surveys for anopheline mosquitoes were conducted throughout the mainland of Papua New Guinea from 1992 to 1998 with the aim of mapping the distribution of the anopheline fauna. Larval collections, adult trap, and human landing collections indicated the presence of seven species (other than those belonging to the Anopheles punctulatus group); these were An. bancroftii, An. annulipes, An, karwari, An. longirostris, An. meraukensis, An. novaguinensis, and An. subpictus. The distribution and ecology of these speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Habitats may be exposed and sunlit [262,472] and larvae are frequently associated with floating algae or other vegetation [164,262,452,476,478] (Table 6). Natural larval habitats for members of the complex include lagoons, shallow ponds, marshes, slow-flowing rivers, natural pools and margins of small streams [12,158,190,191,262,467,470,472,479,480] (Tables 8, 10), but the species are also highly associated with rice fields [12,13,154,158,163,186,190,191,479-483] and irrigation schemes [13,190,479] (Tables 8, 10), specifically in the earlier stages of rice cultivation [13,163,481,482]. Larvae have also been collected from small, artificial containers, including intra-domestic earthen pots, tanks and barrels [16,479] (Table 10).…”
Section: Resultsmentioning
confidence: 99%
“…Habitats may be exposed and sunlit [262,472] and larvae are frequently associated with floating algae or other vegetation [164,262,452,476,478] (Table 6). Natural larval habitats for members of the complex include lagoons, shallow ponds, marshes, slow-flowing rivers, natural pools and margins of small streams [12,158,190,191,262,467,470,472,479,480] (Tables 8, 10), but the species are also highly associated with rice fields [12,13,154,158,163,186,190,191,479-483] and irrigation schemes [13,190,479] (Tables 8, 10), specifically in the earlier stages of rice cultivation [13,163,481,482]. Larvae have also been collected from small, artificial containers, including intra-domestic earthen pots, tanks and barrels [16,479] (Table 10).…”
Section: Resultsmentioning
confidence: 99%
“…pseudobarbirostris with any of the four genotypes. The distribution of these ITS2 genotypes (putative species) has been further investigated [64], indicating distinct distribution for genotypes A, B, and D. Genotype C is sympatric with B and D without evidence of hybridization, suggesting these genotypes are reproductively isolated and likely biological species. Confirmation of this hypothesis using other nuclear genetic markers is needed.…”
Section: Anopheles (Anopheles) Bancroftii Groupmentioning
confidence: 99%
“…Its generally low abundance may be due to its preference for jungle pools associated with dense vegetation for oviposition. Behavioural studies have found it to be zoophilic in some areas [27] and anthropophilic in others [64] and these differences in behaviour may possibly be explained by the presence of cryptic species, each exhibiting different host-feeding preferences [61]. Little is known about the biology of these species and the individual role that each species might play in malaria transmission.…”
Section: Secondary Vectorsmentioning
confidence: 99%
See 2 more Smart Citations